15 No association between systemic arteriosclerosis and atherosclerosis on cardiac MRI and whole body angiography: the tascforce study. (18th May 2017) - Weir-McCall, Jonathan R; Lambert, Matthew; Belch, Jill JF; Cavin, Ian; Gandy, Stephen J; Littleford, Roberta; Macfarlane, Jennifer A; Matthew, Shona Z; Nicholas, RStephen; Struthers, Allan D; Sullivan, Frank; Henderson, Shelley A; et al.
Abstract : Introduction: Arteriosclerosis (arterial stiffening) and atherosclerosis (plaque formation) are pathophysiological processes afflicting the vasculature, both of which are associated with future cardiovascular events. However the degree to which they overlap or simply co-exist is poorly understood. The aim of the current study is to determine if these two processes are significantly associated with one another. Methods: 1651 volunteers with no clinical manifestation of cardiovascular disease and <20% 10-year cardiovascular risk underwent a cardiac MRI and whole body MR angiogram as part of the TASCFORCE study. Systemic arterial stiffness was measured using total arterial compliance (TAC) – calculated as the indexed stroke volume divided by the pulse pressure. Systemic atheroma burden (AB) was calculated by scoring 30 arterial segments within the body based on the degree of stenosis, summating these scores and normalising it to the number of assessable segments. Results: 1515 (574 male, 53.8±8.2 years-old) completed the study.?On multiple linear regression age (B=–0.001 (95%CI –?0.002–−0.000), p=0.004), heart rate (B=–0.003 (95%CI –?0.003–−0.002), p<0.001) and blood pressure (B=–0.008 (95%CI –0.009–−0.008), p<0.001) were independently associated with TAC, while age (B=0.061 (95%CI 0.04–0.08), p<0.001), and smoking pack-year history (B=0.003 (95%CI 0.005), p=0.022) were independently associated with AB. TAC and AB?demonstrated a significant correlation with each other (Spearman rho=–0.12, p<0.001), however on multivariable analysis accounting for age, blood pressure, sex, BMI, smoking status and cholesterol no significant association persisted (B=–?0.001 (95%CI –0.004–0.002), p=0.62). Conclusion: Systemic arteriosclerosis and atherosclerosis are separate entities with each determined by different risk factors. Future efforts in cardiovascular risk prevention should seek to address both of these pathophysiological entities.